3
$\begingroup$

Did I evaluate the following derivative correctly? I know I have not simplified to the utmost extent, but I want to know if this method is correct.

Consider, $\sqrt{1+\sqrt{1+\sqrt{1-2x}}}$

Let A = $1+\sqrt{1+\sqrt{1-2x}}$

Let B = $1+\sqrt{1-2x}$

Let C = $1-2x$

$$\left(\sqrt{1+\sqrt{1+\sqrt{1-2x}}}\right)' = \frac{1}{2}A^{-\frac{1}{2}} \cdot \frac{1}{2}B^{-\frac{1}{2}} \cdot \frac{1}{2}C^{-\frac{1}{2}} \cdot -2 = \frac{-1}{4\sqrt{ABC}}$$

$\endgroup$
4
$\begingroup$

Yes, this is valid. Maybe some explanatory steps in between would help to someone reading it though. It strikes me as not being obvious according to standard well-known derivative rules without a few intermediate steps. $$\begin{align} \left(\sqrt{1+\sqrt{1+\sqrt{1-2x}}}\right)' &= \left(\sqrt{A}\right)'\\ &=\frac{1}{2}A^{-\frac{1}{2}}A'\\ &=\frac{1}{2}A^{-\frac{1}{2}}\left(1+\sqrt{B}\right))'\\ &=\frac{1}{2}A^{-\frac{1}{2}}\frac{1}{2}B^{-\frac{1}{2}}B'\\ &=\frac{1}{2}A^{-\frac{1}{2}}\frac{1}{2}B^{-\frac{1}{2}}\left(1+\sqrt{C}\right)'\\ &=\frac{1}{2}A^{-\frac{1}{2}}\frac{1}{2}B^{-\frac{1}{2}}\frac{1}{2}C^{-\frac{1}{2}}C'\\ &=\frac{1}{2}A^{-\frac{1}{2}}\frac{1}{2}B^{-\frac{1}{2}}\frac{1}{2}C^{-\frac{1}{2}}(-2)\\ &= \frac{-1}{4\sqrt{ABC}} \end{align}$$

$\endgroup$
1
$\begingroup$

Another way to see it is that with $f(x)=\sqrt{1+x}$, and $g(x)=-2x$, you are calculating the derivative of

$$ f\circ f\circ f\circ g(x) $$

then you apply the chain rule.

$\endgroup$
1
$\begingroup$

Another way of thinking about it that makes the use of chain rule on nested functions is like so:

Define $f(x) = \sqrt{1+x}$ and $g(x) = -2x$. Then the original expression $y(x) = f(f(f(g(x))))$, which can be more compactly represented as $y = f^3g$ if we understand that the "exponent" is denoting repeated composition and that the independent variable $x$ that we are differentiating with respect to, is left implicit.

Then application of chain rule immediately gets us:

$y' = f'(f^2g)\cdot f'fg \cdot f'g \cdot g'$

So $y'(x) = \frac 12 (1+ \sqrt{1+\sqrt{1-2x}})^{-\frac 12} \cdot \frac 12(1+\sqrt{1-2x})^{-\frac 12} \cdot \frac 12(1-2x)^{-\frac 12}\cdot (-2)$.

The results should be the same after simplification.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.